Islamic Spirituality Approach in the Development of Students' Religious Character - Moh. Miftachul Choiri (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
The main problem in today’s education is the weakening of students’ religious character due to globalization, digitalization, and moral degradation that diminish spiritual values in daily life. This study aims to analyze the Islamic spirituality approach as a strategy for developing students’ religious character by strengthening inner values, deepening worship practices, and internalizing moral conduct. The method used is library research by reviewing various literature related to Islamic spirituality, Islamic education, religious character formation, and spiritually grounded pedagogical approaches. The findings reveal that the Islamic spirituality approach can enhance students’ religious character through habitual worship, spiritual reflection, reinforcement of school culture, and teacher role-modeling as moral figures. The implications of this study emphasize that integrating Islamic spirituality into the school education system can serve as an effective strategy to overcome moral challenges, improve emotional balance, and build a strong religious identity among students.